2022
DOI: 10.3390/nu14234947
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers’ Perceived Impact of WIC’s Temporary Cash-Value Benefit (CVB) Increases on Fruit and Vegetable Purchasing, Consumption, and Access in Massachusetts

Abstract: Responding to the COVID-19 pandemic, the American Rescue Plan (2021) allowed state agencies of the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) the option of temporarily increasing the Cash-Value Benefit (CVB) for fruit and vegetable (FV) purchases. To examine the impact of this enhancement on WIC caregiver experience, the MA WIC State Office invited 4600 randomly selected MA WIC caregivers to complete an online survey (February–March 2022). Eligible adults had at least one chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Furthermore, WIC participants showed a strong preference for the CVB of $35/child/month to purchase a sufficient amount and variety of FVs to yield a meaningful impact on their families’ diet. These findings align with the previous studies that showed the $35/child/month increased access and redemption of FVs along with an increase in WIC participant satisfaction ( 14 , 16 , 32–34 ). While the caregiver interviews were overwhelmingly positive, some caregivers faced external, structural barriers to CVB redemptions (e.g., lack of awareness of the CVB changes, lack of access to WIC retailers, and inadequate amounts of FVs at WIC retailers).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, WIC participants showed a strong preference for the CVB of $35/child/month to purchase a sufficient amount and variety of FVs to yield a meaningful impact on their families’ diet. These findings align with the previous studies that showed the $35/child/month increased access and redemption of FVs along with an increase in WIC participant satisfaction ( 14 , 16 , 32–34 ). While the caregiver interviews were overwhelmingly positive, some caregivers faced external, structural barriers to CVB redemptions (e.g., lack of awareness of the CVB changes, lack of access to WIC retailers, and inadequate amounts of FVs at WIC retailers).…”
Section: Discussionsupporting
confidence: 92%
“…Greater CVB dollar amounts may have contributed to increased FV redemption amounts and diversity via reduced costs to participants [ 29 ]. This reduction of the relative dollar amount may contribute to increased diversity of redemption through reduced concern about the potential for food waste with the introduction of the child to unfamiliar or less favored FVs [ [29] , [30] , [31] , [32] ] and may further reduce the perceived cost associated with repeated exposure of a child to unfamiliar FVs [ 29 ], which could contribute to increased acceptance of diverse FVs [ 10 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…A proposed revision to the WIC food packages would make the enhanced CVB permanent [ 28 ], pending approval by the US Congress. Prior research identified positive perceptions of the augmented CVB among WIC-participating households in California [ 29 ], Delaware [ 30 ], North Carolina [ 31 ], and Massachusetts [ 32 ]; increases in food security and parental perception of child FV intake in California [ 33 ]; and increases in child FV intake nationally [ 34 ]. The objective of this study was to understand how both the amount and diversity of FVs redeemed at vendors using the WIC CVB changed following the introduction of the augmented benefit in June 2021 using redemption data and price look-up (PLU) codes among WIC-participating households in Los Angeles County, California.…”
Section: Introductionmentioning
confidence: 99%
“…The pandemic also caused unprecedented disruptions in food acquisition behaviors because of factors like stay-at-home orders, fear of contracting the virus, and widespread food shortages [ [9] , [10] , [11] , [12] , [13] , [14] ]. Prior studies focusing on WIC participants during the pandemic have focused on perceptions of and WIC benefit redemption associated with pandemic-related policy changes to the WIC program [ [15] , [16] , [17] , [18] , [19] , [20] ], as well as associations of these policy changes with enrollment [ 21 , 22 ] and self-reported food consumption [ 23 ]. Some studies have used qualitative methods to describe WIC participants’ experiences with purchasing food during the pandemic, such as how participants navigated food shortages or rising food costs [ 18 , 24 ].…”
Section: Introductionmentioning
confidence: 99%